SETS-Based Electronic Module Innovation: Analysis of Students Responses on Waves and Sound Materials - Jaridatul Muniroh; Septania Pratiwi; Ariswan Ariswan; Jumadi Jumadi; Insih Wilujeng (Postgraduate, University of Mataram, 2023)
Technological evolution had a big impact on the world of education, one of them is the progress of teaching materials used in learning. The electronic module (e-Module) is one of the teaching stuff evolution using technological assistance. Electronic modules require innovation in order to have appeal by being integrated into the SETS (Science, Environment, Technology, and Society) learning model. The research aims to describe students responses to the developed electronic module. The research method used is descriptive quantitative research method with the aim of analysis of students responses to the SETS-based e-Module innovation. The response test subjects consisted of 61 students of class VIII C and VIII D of SMP Negeri 2 Depok. The research results of the developed SETS (Science, Environment, Technology, and Society)-based electronic module obtained an average student response test score of 75.16% in the very good category which indicates that the developed electronic module obtained a very good response from students.